Engineering LiNi0.5Co0.2Mn0.3O2/poly(propylene carbonate) interface by graphene oxide modification for all‐solid‐state lithium batteries. Issue 2 (23rd March 2020) - Zhuang, Zilong; Yang, Lezhi; Ju, Bowei; Yin, Ao; Lei, Gang; Zhou, Qian; Tang, Yating; Deng, Zhiyuan; Tu, Feiyue; Qin, Shibiao
Abstract: Electrochemical and chemical interfacial reaction mechanisms between LiNi0.5 Co0.2 Mn0.3 O2 (NMC532) and poly(propylene carbonate) solid polymer electrolyte (PPC‐SPE) are studied. Ni 3+ and Co 4+ species which are electrochemically oxidized from Ni 2+ and Co 3+ during the charging process will induce the decomposition of PPC. Fourier transform infrared spectroscopy (FT‐IR) and 1 H nuclear magnetic resonance (NMR) analysis confirm that the decomposition products of PPC contains ether, which might produce through condensation reaction of alcohol compounds. To retard this side reaction, graphene oxide is applied to coat commercial LiNi0.5 Co0.2 Mn0.3 O2 particles via a facile chemical approach. Compared with pristine cathode, the coated sample displays higher initial capacity, better cycle stability and lower interfacial resistance after cycled. After 300 cycles, the capacity retention is 69.2% at 0.3 C and the resistance is only 25 Ω after 180 cycles. This is due to the graphene layer facilitates the interfacial charge‐transfer process and slows the cathode/electrolyte interfacial side reaction. Consequently, the study illuminated the interface issues of PPC based solid‐state lithium batteries. Abstract :